Pathological investigation of the nephrotoxic effects of the shrub Nolletia gariepina (DC) Mattf. in cattle - Prozesky, Leon (University of Pretoria, 2013)
Dissertation (MMedVet (Pathology))--University of Pretoria, 2004.